Stress response versus stress tolerance: a transcriptome analysis of two rice lines contrasting in tolerance to phosphorus deficiency - Pariasca-Tanaka, Juan; Satoh, Kouji; Rose, Terry; Mauleon, Ramil; Wissuwa, Matthias (Springer, 2009)
Transcriptional profiling has identified genes associated with adaptive responses to phosphorus (P) deficiency; however, distinguishing stress response from tolerance has been difficult. We report gene expression patterns in two rice genotypes (Nipponbare and NIL6-4 which carries a major QTL for P deficiency tolerance (Pup1)) grown in soil with/without P fertilizer. We tested the hypotheses that tolerance of NIL6-4 is associated with (1) internal P remobilization/redistribution; (2) enhanced P solubilization and/or acquisition; and (3) root growth modifications that maximize P interception. Genes responding to P supply far exceeded those differing between genotypes. Genes associated with internal P remobilization/redistribution and soil P solubilization/uptake were stress responsive but often more so in intolerant Nipponbare. However, genes putatively associated with root cell wall loosening and root hair extension (xyloglucan endotransglycosylases/hydrolases and NAD(P)H-dependent oxidoreductase) showed higher expression in roots of tolerant NIL6-4. This was supported by phenotypic data showing higher root biomass and hair length in NIL6-4.